"Wild words" – analyzing angry rhetoric in American politics. Issue 3 (19th November 2018) - Clabough, Jeremiah; Pearcy, Mark
Abstract : Purpose: The purpose of this paper is to explore the use of angry political rhetoric employed by George Wallace and Donald Trump. The authors start by discussing the civic thinking skills stressed within the C3 Framework, specifically the ability to analyze politicians' arguments. Then, the focus shifts to look at angry political rhetoric within the US history. Next, the authors discuss the parallels of the angry political rhetoric employed by both Wallace and Trump. Finally, two activities are provided that enable students to grasp the convergences with the angry political rhetoric utilized by both Wallace and Trump. Design/methodology/approach: In this paper, the authors explore angry rhetoric in American politics. The authors designed two classroom-ready activities by drawing on the best teaching practices advocated for in the C3 Framework. To elaborate, both activities allow students to research and analyze arguments made by George Wallace and Donald Trump. This enables students to engage in the four dimensions of the Inquiry Arc in the C3 Framework. Findings: The authors provide two activities that can be utilized in the high school social studies classroom to enable students to dissect American politicians' messages. These two activities can be adapted and utilized to enable students to examine a political candidate's messages, especially those that draw on angry rhetoric. By completing the steps of these two activities, students are better prepared to be critical consumers of political media messages. Originality/value: In this paper, the authors explore the role of angry political rhetoric in American politics. The authors examine the parallels of political style between George Wallace and Donald Trump. Two activities are provided to help students break down the angry political rhetoric employed by these two controversial figures.